PENGARUH KEBIJAKAN PENENTUAN LOKASI STASIUN PENGISIAN BAHAN BAKAR UNTUK UMUM TERHADAP TINGKAT PENJUALAN BAHAN BAKAR MINYAK PT. PERTAMINA REGION V KOTA SURABAYA - , Ermawaty ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to analyze the differences among types of refueling stations for the General (gas stations) PT. Pertamina Region V city of Surabaya based on the number of sales for Machine Fuel (BBM), the amount of fuel supply to the gas station location, the number of people around the location of the pump and the density of vehicles passing the location of gas stations.Location consists of three types based on the initial process of building stations, where the location of the pump type 1 is âthe location corresponding to thedesignation of PT.Pertaminaâ, type 2 is âthe location of gas stations that do not fit the designation PT.Pertaminaâ and type 3 is âthe location of gas stations that do not fit the designation PT.Pertamina but close to the pump in accordance with the Appropriation PT. Pertaminaâ. Based on the type of pump selected locations each of 30 locations for each type of retail outlets and is representative of all gas stations in the city of Surabaya and represent 31 districts in the area of the city of Surabaya.The results showed that there is a discrepancy between the location of gas stations by type of site that gives effect to the level of fuel sales, the amount of fuel supply, the number of residents around the location of the pump and the density of vehicles based on the test multivariate to see the difference shown by test pillai's trace analysis of the test statistic F of 23.069 with the partial eta squared (PES) of 0.521, test of Wilks lambda test F statistic of 24.899 with the PES of 0.542, test of Hotelling's trace shows the value of the test statistic F of 26.778 with the PES of 0.563 and Testing Roy's largest root shows the value of the test statistic F PES at 41.982 with a value of 0.664 total variance explained, so that H0 is rejected, with Î± = 0.05 it can be concluded that the type of gas station location of PT.Pertamina Surabaya affects the level of fuel sales, the amount of fuel supply, population and vehicle density. Based on estimated marginal means test for the type of gas station location, type of location of the corresponding location type 1 or PT. Pertamina gave the highest contribution to the rate of 6.969 indicated fuel sales, the supply of 9.259, a population of 11.023 and a vehicle at 11, 423. Both the location where the pump type 3 affects the sales of 6.287 percent, the supply of 8.769, a population of 10, 976 and for 10.466 vehicles. Type the location of gas stations last 2 delivers affect on sales of 5.789, a population of 8.355, a population of 11.015 percent and 12.764 of the vehicle. Based on test data Envelopment Analysis (DEA) Location of type 2 there are 3 gas stations. locations are at 100 percent efficiency and 27 retail outlets such as the efficiency level of 83.16 percent to 99.61 percent and the lowest efficiency in the location of the pump type 1 where there are only two locations which achieved an efficiency of 100 percent and 28 other gas stations get an efficiency of 11.29percent to 79.45 percent.